STEROIDAL ALKALOIDS FROM SOLANACEAE SPECIES IN HEMATOLOGICAL MALIGNANCIES: MECHANISMS AND THERAPEUTIC POTENTIAL - Alicja Szymczak; Anna Jaworowicz; Joanna Piasecka; Bartosz Gołembiewski; Grzegorz Mulski; Martyna Manicka; Michał Baranowicz; Weronika Mazurkiewicz; Zuzanna Borecka; Agnieszka Marta Sobczak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Hematological malignancies remain a substantial contributor to global cancer morbidity and mortality, and as such – a major public health issue. Recent evidence has revealed that Solanaceae alkaloids (SAs) could contribute to developing new treatment strategies in hematological oncology. Objective: To critically evaluate contemporary evidence on the anti-cancer effects of SAs, including alpha-solanine, solanidine, solasodine, solamargine, tomatine and tomatidine as well as their potential applicability as bioactive compounds in hematology-related research and therapy. Methods: This narrative review was informed by studies retrieved from widely recognized search engines and databases, including PubMed/MedLine, Google Scholar, ScienceDirect, Wiley, Scopus and Springer Link. The search was conducted using the following MeSH terms: “Solanaceae Alkaloids”, “Solanine”, “Solanidine”, “Solasodine”, “Solamargine”, “Tomatine”, “Tomatidine”, “Leukemia”, “Lymphoma”, “Hematology” and "Blood cancer". Original English-language studies published between 2005 and 2025 were included. Case reports and non-primary data sources were excluded. No meta-analysis was performed. Results: Steroidal alkaloids from Solanaceae species demonstrate significant cytotoxic and anti-proliferative effects against various leukemia and lymphoma cell lines. These compounds have the capacity to inhibit tumor growth and survival through multiple mechanisms, including the induction of apoptosis, oncosis, and cell cycle arrest. Conclusions: Solanaceae-derived steroidal alkaloids exhibit promising antitumor activity in hematological malignancies by modulating apoptosis, survival signaling pathways, and mechanisms of drug resistance. Their ability to enhance chemosensitivity supports further investigation as potential therapeutic or adjuvant agents, pending validation in in vivo and clinical studies.